Personal Branding Model Indonesia Next Top Model (INTM) melalui Instagram - Fatharani Agnia; Tresna Wiwitan (Bandung Conference Series: Public Relations, 2024)
Abstract. Personal Branding of a Flores Cantika model who still adheres to Sundanese as a cultural identity and dares to give an appearance that is more than what it is. Flores is also known for her friendly, kind and humorous nature. This study aims to find out how and why Flores does Personal Branding on Instagram. This study uses a qualitative research method with a case study approach. Through data collection techniques such as interviews, observations, documentation and literature studies. This theory uses Erving Goffman's impression management theory and Peter Montoya's Eight Laws Of Personal Branding concept which explains how the INTM Flores Cantika model's Personal Branding through the Instagram account @florescantika. The results of this study show that in preparing information for posts on Instagram @florescantika in building personal branding, namely by determining goals, determining target followers and forming a team so that the process of building personal branding is easier, then to prepare a visual form in building personal branding on Instagram by choosing a theme or type of content to be uploaded, of course it must be in accordance with personal branding in Flores. Then Flores uploaded her entire portfolio so that the brand would find it easy to see Flores' abilities. Instagram is an alternative media that helps Flores in marketing and promotion, to create new relationships, and advance careers and expand reach easily. Abstrak. Personal Branding seorang model Flores Cantika yang masih melekat berbicara bahasa sunda sebagai identitas budaya dan berani memberikan penampilan yang lebih apa adanya Flores pun dikenal dengan sifatnya yang ramah, baik hati dan humoris. Penelitian ini bertujuan untuk mengetahui bagaimana dan mengapa Flores melakukan Personal Branding di Instagram. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Dengan melalui teknik pengumpulan data seperti wawancara, observasi, dokumentasi dan studi kepustakaan. Teori ini menggunakan Teori impression management Erving Goffman dan konsep Eight Laws Of Personal Branding Peter Montoya yang menjelaskan bagaimana Personal Branding model INTM Flores Cantika melalui akun Instagram @florescantika. Hasil penelitian ini menunjukkan dalam mempersiapkan informasi untuk postingan di Instagram @florescantika dalam membangun personal branding yaitu dengan melakukan penentuan tujuan, menentukan target followers serta membentuk tim agar proses membangun personal branding lebih mudah, kemudian untuk mempersiapkan bentuk visual dalam membangun personal branding di Instagram dengan memilih tema atau jenis konten yang akan di unggah, tentunya harus sesuai dengan personal branding pada Flores. Kemudian Flores mengunggah semua portofolionya sehingga brand akan mudah untuk melihat kemampuan yang Flores miliki. Instagram adalah media alternatif yang membantu Flores di bidang pemasaran maupun promosi, untuk menciptakan relasi baru, dan memajukan karir serta memperluas jangkauan dengan mudah.